2011
DOI: 10.1128/jvi.00131-11
|View full text |Cite
|
Sign up to set email alerts
|

Intercompartmental Recombination of HIV-1 Contributes toenvIntrahost Diversity and Modulates Viral Tropism and Sensitivity to Entry Inhibitors

Abstract: HIV-1 circulates within an infected host as a genetically heterogeneous viral population. Viral intrahost diversity is shaped by substitutional evolution and recombination. Although many studies have speculated that recombination could have a significant impact on viral phenotype, this has never been definitively demonstrated. We report here phylogenetic and subsequent phenotypic analyses of envelope genes obtained from HIV-1 populations present in different anatomical compartments. Assessment of env compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 93 publications
(109 reference statements)
1
60
1
Order By: Relevance
“…Previous studies have shown tissue-specific variations in different viral models, including arenavirus sequences isolated from the same animal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). To avoid this bias, ML29 was isolated only from sera of vaccinated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown tissue-specific variations in different viral models, including arenavirus sequences isolated from the same animal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). To avoid this bias, ML29 was isolated only from sera of vaccinated animals.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 The concept that infected cells and viral particles in semen may arise from distinct genital organs is supported by several elements; thus, the detection of cell-free HIV RNA is not associated with that of cell-associated pro-viral DNA in semen, 14 and subcompartmentalization of HIV quasispecies between seminal cells and seminal plasma has been evidenced. 4,61 Whereas macrophage-tropic R5 strains are readily detected in cell-free seminal plasma, 62 T lymphocytes are the most commonly HIV-infected leukocytes in semen, 63 and pro-viral DNA envelope sequences in seminal cells are primarily not macrophagetropic. 64 This argues against a major contribution of the seminal vesicles to HIV-infected cells in semen because in vitro and in treated men, the bulk of infected cells in this organ is of macrophage nature.…”
mentioning
confidence: 99%
“…In this regard, HIV neurotropism is primarily determined by the viral envelope gene (13)(14)(15)(16), and compartmentalization of a genetically distinct envelope (Env) population in the CNS from that in the systemic circulation (17)(18)(19)(20), as a result of either a founder effect or independent viral adaptive evolution in the brain with long-term HIV infection, has been described (21,22). More-over, different env genotypes have been reported in different CNS regions of HIV-1-infected individuals and simian immunodeficiency virus (SIV)-infected macaques (23)(24)(25)(26), despite the use of a "clonal" inoculum in the latter (23,24), suggesting discordant regional virus evolution in this anatomical compartment, as well.…”
mentioning
confidence: 99%